A Combinatorial Lipid Code Shapes the Electrostatic Landscape of Plant Endomembranes - Platre, Matthieu Pierre; Noack, Lise C; Doumane, Mehdi; Bayle, Vincent; Simon, Mathilde Laetitia Audrey; Maneta-Peyret, Lilly; Fouillen, Laetitia; Stanislas, Thomas; Armengot, Laia; Pejchar, Přemysl; Caillaud, Marie-Cécile; Potocký, Martin; et al. (Developmental cell, 2018)
Membrane surface charge is critical for the transient, yet specific recruitment of proteins with polybasic regions to certain organelles. In eukaryotes, the plasma membrane (PM) is the most electronegative compartment of the cell, which specifies its identity. As such, membrane electrostatics is a central parameter in signaling, intracellular trafficking, and polarity. Here, we explore which are the lipids that control membrane electrostatics using plants as a model. We show that phosphatidylinositol-4-phosphate (PI4P), phosphatidic acidic (PA), and phosphatidylserine (PS) are separately required to generate the electrostatic signature of the plant PM. In addition, we reveal the existence of an electrostatic territory that is organized as a gradient along the endocytic pathway and is controlled by PS/PI4P combination. Altogether, we propose that combinatorial lipid composition of the cytosolic leaflet of organelles not only defines the electrostatic territory but also distinguishes different functional compartments within this territory by specifying their varying surface charges.
Keywords: proteiny huseníčku; fosfatidylseriny; Phosphatidylinositol Phosphates; Arabidopsis; kyseliny fosfatidové; Plant Roots; signální transdukce; fosfatidylinositolfosfáty; Static Electricity; Arabidopsis Proteins; Signal Transduction; organely; kořeny rostlin; Cell Membrane; Organelles; statická elektřina; buněčná membrána; Phosphatidylserines; Phosphatidic Acids